2020
DOI: 10.1039/d0sc03519j
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclization of bis-indole quinolines for selective stabilization of G-quadruplex DNA structures

Abstract: Macrocyclization improves the selectivity, affinity, and ability to stabilize G4 DNA structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…42 Performed at a constant temperature, this method is suitable to characterise of strong binders with K d values down to few nM, and is gaining increasing popularity in Please do not adjust margins Please do not adjust margins characterizing ligand-G4 interactions. 13,43 The results of titrations, performed with four fluorophore-labelled G4-DNA oligonucleotides belonging to different folding topology groups (Pu24T and myc22: parallel, 25TAG: hybrid, 22CTA: antiparallel, sequences: cf. Table S1 †), confirmed the G4binding properties of novel derivatives (Table 1, titration curves: Fig.…”
Section: Figmentioning
confidence: 99%
“…42 Performed at a constant temperature, this method is suitable to characterise of strong binders with K d values down to few nM, and is gaining increasing popularity in Please do not adjust margins Please do not adjust margins characterizing ligand-G4 interactions. 13,43 The results of titrations, performed with four fluorophore-labelled G4-DNA oligonucleotides belonging to different folding topology groups (Pu24T and myc22: parallel, 25TAG: hybrid, 22CTA: antiparallel, sequences: cf. Table S1 †), confirmed the G4binding properties of novel derivatives (Table 1, titration curves: Fig.…”
Section: Figmentioning
confidence: 99%
“…To overcome some of the challenges associated with targeting G4 DNA, macrocyclic compounds can offer a beneficial starting point in terms of ligand design [30] . Macrocycles have been shown to enable design of compounds with good oral pharmacokinetic (PK) properties when operating in the challenging chemical space termed “beyond rule of 5” [31] .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we have shown that macrocyclization can indeed be a powerful tool to generate compounds that strongly bind and stabilise G4 structures while still showing complete selectivity towards G4 DNA over double‐stranded DNA [30] . Here, we have further explored this approach and used it as an example in combination with well‐known ligands to delineate key properties for efficient G4 ligand design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human telomeres are single-stranded overhangs of a hexanucleotide (TTAGGG) repeat unit, which are known to adopt antiparallel G-quadruplex conformation in solution . This structure is polymorphic, and subtle changes in the base composition, position, salt type, ionic strength, and hydration are known to modulate its conformational ensembles. Many efforts have been made over the past two decades to discover G-quadruplex targeting ligands of both synthetic and natural origins. A general picture that has emerged from these studies indicates that G-quadruplex binding molecules usually contain extended π-conjugation over a well-spread flat surface, such as those found in fused aromatic rings or macrocyclic systems containing additional interaction centers to enhance binding.…”
Section: Introductionmentioning
confidence: 99%